Education and development: thirty years of continuity and change - McGrath, Simon (Elsevier, 2010)
At the end of the thirtieth volume of IJED and in the year that the journal published its 1000th paper, it is appropriate to look back at the journal’s development. In so doing, this article will discuss a series of important issues regarding the future of the field of international education and development and how it engages with development studies. The paper concludes that the challenge for IJED and for the wider work of its readership is to start imagining a more radical future in which we seek more purposefully to build bridges with other disciplines, engage with new methodological tools and encourage fresh voices but above all else communicate more clearly what we do and don’t know about the wonderful complexity of the education-development relationship.